Effects of Manipulation of Forage and Concentrate in Diets of Murrah Buffalo on Production and Reproduction - Kumar, Ravi (Indian Journal of Animal Nutrition, 2021)
A study of six month duration was conducted to evaluate the effect of dietary management on production and reproduction performance in lactating Murrah buffalo. Eighteen lactating Murrah buffaloes were assigned to three dietary treatment groups with six animals in each group based on parity. Control group (T1) was fed wheat straw, green fodder and concentrate mixture based diet in the ratio of 30:35:35 as per ICAR (2013) standards. Crude protein and total digestible nutrients contributed by green fodder of control group ration wasreplaced with concentrate mixture at 30% and 40% level in group T2 and T3, respectively in an iso-nitrogenous and iso-caloric manner. Dry matter intake, milk yield, 6% fat corrected milk yield, solid-not-fat and total solids were reported to be significantly (P